Development of Economic Skills in Schoolchildren - Zaleskienė, Irena (Acta Paedagogica Vilnensia, 1993)
According to the analysis of philosophical, sociological and pedagogical literature, experience of primary school working education, long-term monitoring of schoolchildren’s practical work, economic skills are defined as of practical abilities that enable productive action and guide the character to the economical relation with time, place and working tools. This paper presents progress and results of an educational experiment, which took place in the second grade of Vilnius schools. Several formative stages of the experiment were intended to form: 1) preservation and conservation skills of the primary school pupils (personal belongings, work tools, tools for shared use); 2) skills of planning (working materials, work processes, spending time and money); 3) the skills of rational work place management (selecting and arranging equipment, maintaining cleanliness during work, tidying out the place on completion of work). Successful results of the experiment were ensured by close cooperation between schools and families, appropriate selection of practical tasks, taking into account the given level of skills and individual psychophysical characteristics of children.